High Selectivity Microstrip Bandpass Filter Integrate With Ring Resonator Bandstop Filter - Mutalib, Mohamad Ariffin; Zakaria, Zahriladha; Shairi, Noor Azwan (Penerbit Universiti, UTeM, 2017)
An integrated high selectivity microstrip wideband bandpass filter with ring resonator bandstop filter is presented in this paper. The bandpass filter consists of of 6 th λ⁄4 short circuited stubs and two-sections of open circuited stub at one end of the element. The integration with bandstop filter is realized using ring resonator. The experimental result shows that the bandwidth of the wideband bandpass filter is between 2.9 GHz – 5.8 GHz. The bandstop filter produced high selectivity and attenuation at resonant frequency of 5.05 GHz and Q-factor of 252.2. This type of filter is suitable for applications such as the multi-service and multiband communication system in order to discriminate the undesired signals.